A Cross-Sectional Assessment of Cutaneous Lumbosacral and Coccygeal Physical Examination Findings in a Healthy Newborn Population. (1st February 2018) - Aby, Janelle; Kim, Juliann Lipps
Objective. The purpose of this study is to describe the range and frequency of cutaneous lumbosacral and coccygeal findings encountered during the newborn examination in a population of apparently healthy babies, to determine if the prevalence of these findings is associated with race/ethnicity, and to report the frequency of co-occurrence of low-risk cutaneous findings. Methods . Lumbosacral physical findings of 1121 infants were documented on well newborns at least 35 weeks or greater gestational age under the authors' care. The overall frequency of each physical finding was tabulated in addition to determining whether frequencies varied by race/ethnicity. Co-occurrence of the most common physical findings was also examined. Results . Of 1096 infants included in the study, 24.8% had deviated or duplicated gluteal creases, 15.6% had dimples, and 24.7% had lumbosacral and/or coccygeal hairiness. All racial/ethnic groups had double to quadruple the risk of lumbosacral hair when compared with Caucasians. A total of 44.1% of study infants had lumbosacral/coccygeal slate-grey patches, which were least common in Caucasians. Seven infants had coccygeal skin tags, and 14 infants had lumbosacral vascular macules. Thirty-one percent had more than 1 cutaneous lumbosacral finding present, 24.8% had 2 findings, and 6.2% had 3 or more findings. Conclusion . Coccygeal dimples, increased lumbosacral and/or coccygeal hair, deviations and/or duplications of the gluteal crease, and lumbosacral slate-grey patches are common in healthy newborns and vary by race/ethnicity. Eleven percent of study infants had 2 or more low-risk cutaneous findings excluding slate-grey patches. Distinction between low-risk and common versus high-risk findings is important when deciding which patients need further evaluation.